The impact of hepatocyte-specific deletion of hypoxia-inducible factors on the development of polymicrobial sepsis with focus on GR and PPARα function - Vanderhaeghen, Tineke; Timmermans, Steven; Eggermont, Melanie; Watts, Deepika; Vandewalle, Jolien; Wallaeys, Charlotte; Nuyttens, Louise; De Temmerman, Joyca; Hochepied, Tino; Dewaele, Sylviane; Berghe, Joke Vanden; Sanders, Niek; et al. (Frontiers in Immunology, 2023)
Introduction Polymicrobial sepsis causes acute anorexia (loss of appetite), leading to lipolysis in white adipose tissue and proteolysis in muscle, and thus release of free fatty acids (FFAs), glycerol and gluconeogenic amino acids. Since hepatic peroxisome proliferator-activated receptor alpha (PPARα) and glucocorticoid receptor (GR) quickly lose function in sepsis, these metabolites accumulate (causing toxicity) and fail to yield energy-rich molecules such as ketone bodies (KBs) and glucose. The mechanism of PPARα and GR dysfunction is not known. Methods & results We investigated the hypothesis that hypoxia and/or activation of hypoxia inducible factors (HIFs) might play a role in these issues with PPARα and GR. After cecal ligation and puncture (CLP) in mice, leading to lethal polymicrobial sepsis, bulk liver RNA sequencing illustrated the induction of the genes encoding HIF1α and HIF2α, and an enrichment of HIF-dependent gene signatures. Therefore, we generated hepatocyte-specific knock-out mice for HIF1α, HIF2α or both, and a new HRE-luciferase reporter mouse line. After CLP, these HRE-luciferase reporter mice show signals in several tissues, including the liver. Hydrodynamic injection of an HRE-luciferase reporter plasmid also led to (liver-specific) signals in hypoxia and CLP. Despite these encouraging data, however, hepatocyte-specific HIF1α and/or HIF2α knock-out mice suggest that survival after CLP was not dependent on the hepatocyte-specific presence of HIF proteins, which was supported by measuring blood levels of glucose, FFAs, and KBs. The HIF proteins were also irrelevant in the CLP-induced glucocorticoid resistance, but we found indications that the absence of HIF1α in hepatocytes causes less inactivation of PPARα transcriptional function. Conclusion We conclude that HIF1α and HIF2α are activated in hepatocytes in sepsis, but their contribution to the mechanisms leading to lethality are minimal.